Strategi Komunikasi P3KA Dalam Meningkatkan Prestasi Mahasiswa UHAMKA - Marwa Ulfa; Lisa Rosita; Nabiilah (Brand Communication, 2022)
In the process of delivering messages, a Communication Strategy is needed so that the messages conveyed are effective and in accordance with what is expected, UHAMKA which is a Muhammadiyah higher education institution (PTM) has a goal to be able to give birth to students who have achievements, one of which is academic achievement, in achieving goals The University Leaders are assisted by a central institution for the development and development of UHAMKA Student Affairs and Alumni (P3KA). The purpose of the research with the title P3KA Communication Strategy in Improving UHAMKA Student Achievement is to understand how P3KA's communication strategy in Improving UHAMKA Student Achievement is. This research uses a case study method to the P3KA team and data collection techniques through interviews and non-participant observations. The results of this study show that P3KA uses a communication strategy starting from the planning, implementation and evaluation stages